2013
DOI: 10.3390/v5102469
|View full text |Cite
|
Sign up to set email alerts
|

West Nile Virus Antibody Prevalence in Horses of Ukraine

Abstract: West Nile virus (WNV) is a mosquito-borne virus of global importance. Over the last two decades, it has been responsible for significant numbers of cases of illness in humans and animals in many parts of the world. In Ukraine, WNV infections in humans and birds were first reported more than 25 years ago, yet the current epidemiological status is quite unclear. In this study, serum samples from over 300 equines were collected and screened in order to detect current WNV activity in Ukraine with the goal to estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The high occurrence of WNV in horses in Israel in the last decade is also demonstrated by the high FOI detected in this study, with 12.3% and 22.3% FOI in 2002 and 2013, respectively. It could be argued that the increase in seroprevalence demonstrated in this study between 2002 and 2013 could be a result of different antibody detection methods, as the ELISA method used for the 2013 samples is considered more sensitive than the SN method used for the 2002 samples [31] ; however, it has previously been shown that WNV-neutralizing test was able to confirm 42 out of 49 ELISA-positive horse sera (86%) [32] . Furthermore, in addition to the ELISA method, serum neutralization (SN) test was also employed on the 2013 samples, as was previously performed to evaluate WNV seroprevalence in horses in Germany [33] , and excellent agreement was demonstrated between the two detection methods with a kappa of 86.4% (p value <0.001), further supporting the validity of the ELISA results and the conclusions drawn from them.…”
Section: Discussionmentioning
confidence: 70%
“…The high occurrence of WNV in horses in Israel in the last decade is also demonstrated by the high FOI detected in this study, with 12.3% and 22.3% FOI in 2002 and 2013, respectively. It could be argued that the increase in seroprevalence demonstrated in this study between 2002 and 2013 could be a result of different antibody detection methods, as the ELISA method used for the 2013 samples is considered more sensitive than the SN method used for the 2002 samples [31] ; however, it has previously been shown that WNV-neutralizing test was able to confirm 42 out of 49 ELISA-positive horse sera (86%) [32] . Furthermore, in addition to the ELISA method, serum neutralization (SN) test was also employed on the 2013 samples, as was previously performed to evaluate WNV seroprevalence in horses in Germany [33] , and excellent agreement was demonstrated between the two detection methods with a kappa of 86.4% (p value <0.001), further supporting the validity of the ELISA results and the conclusions drawn from them.…”
Section: Discussionmentioning
confidence: 70%
“…For example, in Slovak Republic, the reported seropositivity was 8.3% in 2008–2011, 4.8% in 2012 and 0% in 2013 [ 42 , 43 ]. However, a higher proportion of seropositive horses (13.5%) was detected in 2010–2011 in Ukraine [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…pipiens are both potential vectors of West Nile virus that recently appear in more European countries (Table 2). In Ukraine this pathogen caused an epidemic in 1985 with 38 patients (Hubálek and Halouzka, 1999;Ziegler et al, 2013). Between 2007 and 2016 the total number of cases was 86.…”
Section: Resultsmentioning
confidence: 99%